Psychophysiology, performance, and training under stress in police service - Voigt, Laura (2021)
Police officers perform far-reaching actions while facing a variety of operational and organizational stressors. Although acute psychophysiological stress responses can be adaptive, chronic or frequent stress might alter officers’ physiological functioning. Critically, stressful situations are often associated with performance failures, especially when resources are depleted. Hence, the essential challenge for police training is to teach skills that transfer to high-stress situations. To protect police officers’ occupational performance and long-term health, the dissertation aimed at gaining a comprehensive understanding of stress processes in police service and using the insights to design evidence-based training methods. Building on the cognitive appraisal theory, in Manuscript 1, the psychological appraisal processes underlying perceived stress in police service were assessed in a mixed-methods online survey in a sample of 2567 European police officers during the COVID-19 pandemic. Inter-individual differences in stressor appraisal and perceived coping resources explained the large inter-individual variance in self-reported stress. Manuscript 2 focused on the idiosyncratic associations of perceived stress and physiological stress markers of a 28-year-old male police officer in an ecological momentary assessment over three weeks (90 data points). The daily profiles of salivary cortisol and alpha-amylase were dysregulated suggesting a state of allostatic load. Pointing to hyporesponsivity, cortisol and alpha-amylase were not related to perceived stress in daily life and did not increase in police incidents. The preregistered study in Manuscript 3 investigated the influence of emotional and physical stress on response inhibition in a sample of 24 university students. Contrary to the predictions by the attentional control theory, neither emotional nor physical stress significantly altered inhibitory performance. Based on the constraints-led approach, Manuscript 4 presented a literature-based analysis of strengths, weaknesses, opportunities, and threats associated with the implementation of police training under stress in Virtual Reality. Building on the empirical findings, Manuscript 5 demonstrated how evidence on perceived stressors can inform police training under stress. Together, the results of the dissertation point towards a discrepancy between psychological, physiological, and behavioral stress responses, potentially mediated through interindividual differences in stress reactivity and stress-dose effects. Adressing the complexity of stress in police training provides officers with the opportunity to actively engage in coping, adapt to stressors, and eventually grow from stress. To bridge the gap between science and practice, further research is needed to facilitate the implementation of evidence-based training methods into police service.
Keywords: Hochschulschrift